Pengaruh Kesadaran Pajak dan Implementasi Sistem Samsat Drive Thru terhadap Kepatuhan PKB Roda Dua di Samsat Jakarta Utara: (Studi pada Generasi Z) - Venina Febrianti; Joelianti Dwi Supraptinignsih; Sopian Sopian (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the effect of taxpayer awareness and the implementation of the Samsat Drive Thru system on the level of compliance with Motor Vehicle Tax (PKB) payments at the North Jakarta SAMSAT among Generation Z registered at the North Jakarta Samsat. Generation Z as a productive age group and significant motor vehicle users has an important role in regional tax revenues. The research method used is quantitative with a survey approach. Data were collected through questionnaires that were distributed boldly and attractively to Generation Z respondents who met the criteria. Data analysis was carried out using inferential statistical techniques to test the hypothesis regarding the direct effect of taxpayer awareness and the implementation of the Samsat Drive Thru system on compliance with PKB payments. The results of the study are expected to provide a deeper understanding of the factors that influence the fulfillment of PKB payments among Generation Z, especially the role of taxpayer awareness and the effectiveness of the implementation of the Samsat Drive Thru system